Anisotropic acoustical properties of sintered fibrous metals. (11th February 2015) - Meng, H.; Ao, Q.B.; Ren, S.W.; Xin, F.X.; Tang, H.P.; Lu, T.J.
Abstract: A combined theoretical and experimental study is carried out to investigate the anisotropic acoustic properties of sintered fibrous metals. In the theoretical model, based on the transversal and longitudinal dynamic mass densities and effective bulk modulus of randomly placed parallel fibers, the dynamic mass densities and effective dynamic bulk modulus of a sintered fibrous metal in the direction normal and parallel to its surface are obtained. Sound absorption coefficient, sound speed and attenuation coefficient in each of the two directions are calculated once the dynamic mass densities and effective dynamic bulk modulus are determined. For validation, experimental measurements are performed, with good agreement between theoretical prediction and measurement data achieved. Subsequent numerical investigations focus on the influence of fiber diameter and porosity on the anisotropic acoustical properties of the sintered fibrous metal. The sintered fibrous metal exhibits better sound absorption/attenuation performance in the parallel direction than in the normal direction. The anisotropy in acoustical properties increases with decreasing fiber diameter and porosity due mainly to increasing interactions between adjacent fibers.